Penggunaan Kata Baku dan Tidak Baku di Beberapa Tempat di Pamekasan - Dzakiyah Nur Anisa Santoso; Astri Carine; Ardheta Bintang Rahmadena; Muhammad Alfirdaus (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This study aims to thoroughly examine the phenomenon of the use of standard and non-standard words found in various types of written texts in public spaces, particularly in promotional media and visual information. The method employed is qualitative descriptive with a content analysis approach. Data were obtained through direct observation of visual elements in public spaces and analyzed with the support of literature from previous studies, including social media posts that reflect the everyday language habits of the community. The study focuses on various visual media such as banners and business signboards that display language use. The results indicate a significant gap between the language rules stipulated in the General Guidelines for Indonesian Spelling (PUEBI) and the Big Indonesian Dictionary (KBBI) and the language practices developed in society. Several factors influencing the use of non-standard words include the community's habitual use of certain forms, the inheritance of habits from previous generations, and the influence of foreign languages and local dialects. The consequences of this phenomenon may include misunderstandings in communication and challenges in maintaining the standard and purity of Indonesian as the national language.